Management Analysis of Organizing and Public Contribution of “Pondok Tetirah Dzikir” Borstal Rehabilitation - Abdul Choliq Hidayat; Aulia Aulia; Aftoni Sutanto; Agus Siswanto (Forum Inovasi Bisnis dan Manajemen, 2022)
The purpose of this study is to reveal one's efforts to independently provide alternative solutions for the rehabilitation of neuro-insane lunatics or narcotics, or others by the method of Inabah Suryalaya, Tasikmalaya. The way of Thariqah Qadiriyah Wa Naqsyabandiyah is to perform prayers, fasting, Dhikr, reciting the Qur'an, and bathing taubah. Method of this research was qualitative approach, survey, interview and exploration. The result this research proved that this institution practiced the modern management philosophy: planning, organizing, actuating, and evaluating. This research explored the way of management sight to figure out organizing and contributing borstal rehabilitation, in order to encourage people to participate and contribute. The basic philosophy of patient rehabilitation is humanistic treatment, high empathy, brotherhood, not really insane, not exiled person, et cetera. But feel homy, freely to act, needness of each other, humanistic exploration, take and give to each other.